Traffic behavior of local area network (ethernet) based on queuing models and its quality of service / Kayvan Atefi - Atefi, Kayvan (2012)
Nowadays, Local area networks (LAN) are one of the most popular networks, and the LAN performance is very important for operators. The Local Area Network method has been applied as an essential infrastructure of numerous companies and organizations for a long time. Thus, this issue has create the network topological structure which continues to be elevated for that scientists and engineers to resolve, due to its foundational status within the network application. On the other hand, analyzing performance is consisted of examining counter values which are reported while the system is performing with various operations. Furthermore, there is some queuing model in this research which will focus on M/M/l and M/M/c queuing model and also some parameters that can be used for analyzing LANs namely delay utilization and throughput that will be covered in this research. Performance Analysis on LAN have been investigated by different researchers, but there is not any strict research about Performance Analysis of queuing model at LAN. Thus, there are some problems in analyzing performance of LAN at queuing model that will be solved in this research. The purpose of this research is based on the objectives of this study which evaluates types of queuing model in LAN and compares the traffic behavior of these queuing models in terms of essential parameters. Moreover, to develop, design and implement a simulation model to perform the simulation of M/M/l and M/M/c queuing model with different metrics and at last analyzing the results to evaluate traffic behavior of queuing model in LAN. For conducting this research, the researcher has implemented some methods as following sequences: Firstly, during the preliminary study and knowledge acquisition, a logical understanding is done as the background of study and problem justification which is continued on an empirical study which is done to verify the set of results in the system prototype, when all of data are gathered, M/M/l and M/M/2 queuing model are implemented in LAN via OPNET simulator. Finally, the system evaluation prepares a complete report of the research, and then it will be designed to performance analysis of these queuing models in LAN to evaluate number packet delay, utilization and throughput. After implementing the simulation according to achieved the result which shows that when the number of clients has been increased, delay and utilization will also be increased, because with increasing the clients, servers will be busier so the utilization will be increased. However, when the clients are increased the throughput will decrease. Also Moreover, when the researcher uses M/M/1 queuing system, the researcher have more delay rather than having M/M/2 and also have more utilization when use M/M/1. Nevertheless, when the researcher uses M/M/2 system, have a higher throughput compare to M/M/1.